Motherhood in Johannesburg: mapping the experiences and moral geographies of women and their children in the city - Parker, Alexandra; Rubin, Margot (My University, 2017)
South African cities were designed and legislated to enforce spatial marginalisation of Africans, coloureds and Indians to peripheral urban settlements. The legacy of this intentionally constructed racially segregated space has been reinforced in the post-apartheid period by market forces around property prices, informal settlement of land, and the unintended consequences of state housing policy, amongst other factors. Patterns of race-based spatial marginalisation have also been overlaid by income and gender factors, creating hostile conditions for women, and poor women in particular. Whilst there is a rich mine of literature on spatial exclusions due to race, very little study has focused on the gendered spatial experiences of women, and more particularly mothers, in South African cities. Mothers sustain a number of multifaceted roles through, and beyond, the care of and provision for their children. They engage in multiple spheres of work, home, education, community and politics. Straddling these various realms, mothers are increasingly active ‘users’ of a diversity of city spaces. In some cases, the daily routines of mothers are confined within a single neighbourhood, but most often mothers enact their many roles on a day-to-day basis in many different areas of the city. The nature of motherhood (as both a relationship of care and a role constructed in society) and highly unequal urban conditions often impose heavy burdens – financial, temporal and emotional. However, the choices mothers make in the city by traversing diverse spaces in order to fulfil their multiple roles, and the responsibilities and costs this inflicts, is not well understood. This Occasional Paper speaks to this ‘gap’ by exploring the spatial dynamics of mothers in Johannesburg. It investigates how women who self-identify as mothers navigate their own and their families’ daily lives in the city in facing a variety of challenges and obstacles. Methodologically the research involved studying the everyday practices and experiences of 25 mothers in the city, who agreed to in-depth interviews and mapping exercises. The participants were a diverse group in terms of geographic location, income, race, age, and family situation. The women narrated their daily lives and the routes they took through various places and spaces that made up their everyday experiences of the city. They discussed their decision-making around the choice of home, work, school, shopping and recreation and detailed the social and spatial dynamics of their support networks. Exploring these ‘moral geographies’ of motherhood provides valuable insights into a group of people who engage the city extensively in ways that are under-recognised. In turn, understanding the spatial negotiations that typify mothers’ lives exposes the depth of spatial inequality and poor urban management of our city-region in new ways. This Occasional Paper is the result of a partnership between the South African Research Chair in Spatial Analysis and City Planning (SA&CP) and the GCRO, and specifically involved a collaboration between researchers Yasmeen Dinath, Margot Rubin and Alexandra Parker.
Keywords: mothers; children; identity; mapping; space